A CFD approach for the flow regime transition in a vane-type gas-liquid separator. (February 2023) - Yin, Junlian; Zhang, Tingting; Krull, Benjamin; Meller, Richard; Schlegel, Fabian; Lucas, Dirk; Wang, Dezhong; Liao, Yixiang
Highlights: A novel transfer model between dispersed phase and continuous phase has been proposed based on experimental results. The transfer model has been incorporated into OpenFOAM-Hybrid model to predicted multi-field two-phase flows. With the help of the Extending OpenFOAM-Hybrid, the stability of gas core in the vane-type separator is investigated. Abstract: Two-phase flows generally occur with various flow regimes, even in fixed geometries. The transition from one regime to another requires careful numerical modeling. In vane-type gas-liquid separators, the transition from bubbly flow to stratified flow is the dominating phenomena. This paper describes the application of a morphology adaptive multifield two-fluid model (OpenFOAM-Hybrid, Meller et al., Int J Numer Methods Fluids, 93(3), 748-773) to predict the complex flow in such a kind of vane-type separator, covering different regimes and the corresponding transitions. By means of OpenFOAM-Hybrid, the coexistence of dispersed bubbles and continuous gas core is modelled simultaneously with the same set of equations. The key issue here is the definition of a morphology transition criterion describing the formation of continuous gas out of dispersed gas. Such a transition criterion, based on the local volume fractions of the dispersed and the continuous gas phase, is proposed. It combines coalescence and absorption transfer processes. This model is added to OpenFOAM-Hybrid and validated by predicting both gas bubbles and a continuous gas core as well as transitional regimes in the vane-type separator. The gas core morphology evolution is investigated in detail. OpenFOAM-Hybrid is capable of capturing the gas core dynamics in the vane-type separator and thus proves to be a reliable predictive tool.